Investigation on the effect of "nano-powder" in micro-wire electro-discharge machining (μ-WEDM) process for fabricating micro actuators with nanometric mirror surface - Saleh, Tanveer; Bhuiyan, Moinul; Abdul Muthalif, Asan Gani (2017)
The aim of this project was to carry out fundamental investigation on the nano-powder assisted wire EDM fabrication process for micro mirror. The WEDM machine at International Islamic University Malaysia was used. Different quantity and size of conductive nano-powder will be used along with the dielectric liquid to improve the surface quality of micro mirror. The surface roughness and optical reflectivity will be investigated thoroughly with standard equipment which will corelated with the various process parameters. The target of roughness of surface around Ra(50nm). Successful completion of the project will lead to characterization of new type of nano-powder assisted WEDM process.